2017
DOI: 10.4049/jimmunol.1601695
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib and Nilotinib Off-Target Effects on Human NK Cells, Monocytes, and M2 Macrophages

Abstract: Tyrosine kinase inhibitors (TKIs) are used in the clinical management of hematological neoplasms. Moreover, in solid tumors such as stage 4 neuroblastomas (NB), imatinib showed benefits that might depend on both on-target and immunological off-target effects. We investigated the effects of imatinib and nilotinib on human NK cells, monocytes, and macrophages. High numbers of monocytes died upon exposure to TKI concentrations similar to those achieved in patients. Conversely, NK cells were highly resistant to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Therefore, leukocytes are unlikely contribute to nilotinb-exacerbated atherogenesis because they did not increase after nilotinib treatment. This observation is in line with a latest publication that nilotinib induces necrosis in monocytes and inhibits their differentiation into macrophages (26).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, leukocytes are unlikely contribute to nilotinb-exacerbated atherogenesis because they did not increase after nilotinib treatment. This observation is in line with a latest publication that nilotinib induces necrosis in monocytes and inhibits their differentiation into macrophages (26).…”
Section: Resultssupporting
confidence: 92%
“…In accordance, regulatory T cells are maintained within the bone marrow and can migrate along the CXCR4-CXCL12 axis ( 92 ). Regarding modulation of CXCR4 expression using pharmacological agents, tyrosine kinase inhibitors (TKIs) imatinib and nilotinib have been shown to selectively increase the cell surface of CXCR4 on NK cells and monocytes, in vitro experiments using NK cells derived from neuroblastoma patients ( 93 ).…”
Section: Cxcr4 and Its Ligand Cxcl12mentioning
confidence: 99%
“…Along this line, during imatinib mesylate therapy in GIST patients, the frequency of NK cells did not change in fibrous trabeculae, whereas significantly increased in the core of both localized or metastatic tumors, an observation that correlated with a better prognosis ( 78 ). Interestingly, a recent study analyzing the off-target effect of imatinib mesylate on immune cells showed that this drug causes a significant up-regulation of CXCR4 in both T and NK cells ( 86 ). Accordingly, NK cells ex-vivo isolated from peripheral blood of chronic myeloid leukemia patients receiving imatinib mesylate showed levels of CXCR4 significantly higher than those detected in healthy individuals ( 86 ).…”
Section: Nk Cells In Tumor Tissuesmentioning
confidence: 99%